ANALISIS FAKTOR FAKTOR YANG MEMPENGARUHI PERSISTENSI LABA PADA PERUSAHAAN MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 – 2017 - Lasrya, Elsa; Ningsih, Oktavianiwiari (Yayasan Pendidikan Riset dan Pengembangan Intelektual (YRPI), 2020)
The purpose of this study was to determine whether the independent variables, namely Cash Flow Volatility, Sales Volatility, Debt Levels and Operating Cycles affect the dependent variable, namely Profit Persistence. The sampling technique uses Purposive Sampling where 60 samples are used. This study uses multiple linear regression analysis techniques, F test and t test to determine its effect. The results of this study indicate that partially Cash Flow Volatility and Debt Levels affect Profit Persistence while the other two variables Sales Volatility and Operating Cycle have no effect on Profit Persistence. And simultaneously the four Independent variables influence the Profit Persistence.